On Disturbed Time Continuity in Schizophrenia: An Elementary Impairment in Visual Perception? - Giersch, Anne; Lalanne, Laurence; Van Assche, Mitsouko; Elliott, Mark (Frontiers in Psychology, 2013)
Schizophrenia is associated with a series of visual perception impairments, which might impact on the patients’ every day life and be related to clinical symptoms. However, the heterogeneity of the visual disorders make it a challenge to understand both the mechanisms and the consequences of these impairments, i.e. the way patients experience the outer world. Based on earlier psychiatry literature, we argue that issues regarding time might shed a new light on the disorders observed in patients with schizophrenia. We will briefly review the mechanisms involved in the sense of time continuity and clinical evidence that they are impaired in patients with schizophrenia. We will then summarize a recent experimental approach regarding the coding of time-event structure in time, namely the ability to discriminate between simultaneous and asynchronous events. The use of an original method of analysis allowed us to distinguish between explicit and implicit judgements of synchrony. We showed that for SOAs below 20 ms neither patients nor controls fuse events in time. On the contrary subjects distinguish events at an implicit level even when judging them as synchronous. In addition, the implicit responses of patients and controls differ qualitatively. It is as if controls always put more weight on the last occurred event, whereas patients have a difficulty to follow events in time at an implicit level. In patients, there is a clear dissociation between results at short and large asynchronies, that suggest selective mechanisms for the implicit coding of time-event structure. These results might explain the disruption of the sense of time continuity in patients. We argue that this line of research might also help us to better understand the mechanisms of the visual impairments in patients and how they see their environment.